Research in codec optimization and the application of SP-frame in H.264/AVC - Yifeng Liu; Chuangbai Xiao; Ligang Zhen (2009 International Conference on Image Analysis and Signal Processing, 2009)
The new SP-frame, which can replace intra-frame, is used for bitstream switching. In this paper, first, the SP-frame's main applications are introduced; second, by analyzing the original SP-frame coding process, the new scheme is proposed, which allows drift-free bitstream switching; finally, a lot of simulation results are used to compare SP-frame coding efficiency with other frames. The experimental results indicate, SP-frame coding efficiency is near P-frame's, but much higher than Intra-frame's. Compared with the P-frame, the SP-frame can afford such a function; at the same time, the SP-frame can reduce bit rate compared with Intra-frame.